Pengabdian kepada Masyarakat melalui Digitalisasi dalam Meningkatkan UMKM di Desa Suka Makmur Kabupaten Langkat - Prames Wary Tri Wulandari; Misrah Misrah; Khairida Nur Rahmah; Satria Budi; Radiansyah Radiansyah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This community service activity was conducted by the Community Service Program (KKN) team in Suka Makmur Village, Langkat Regency. The activity aimed to improve the digital literacy of Micro, Small, and Medium Enterprises (MSMEs) who are still limited in utilizing digital technology. This effort was carried out through training on